Correlation Between Student Learning Motivation and Learning Quality on Student Critical Thinking Skill on Atomic Structure Material - Ananta Aryabima; Nurhayati, Sri; Sumarni, Sri Susilogati (Universitas Negeri Semarang, 2025)
Education in the 21st century demands skills that must be mastered. The skills that students must have in the 21st century are called 4C, namely critical thinking, creativity, communication skills, and collaboration. The education system in Indonesia currently implements a kurikulum merdeka that focuses on developing the character and competence of students and focuses on essential materials. This study aims to determine the correlation between learning motivation and learning quality on critical thinking skills. Critical thinking skills are one of the skills that students must master in the 21st century. This study is a quantitative model study with a survey method. The sample used in this study was 103 students from grades X-E 5, X-E 10, and X-E 11 of SMA Negeri 12 Semarang. Data analysis was carried out using PLS-SEM. The results of the hypothesis test using PLS-SEM showed that learning motivation did not have a positive and significant correlation with critical thinking skills with a p-value of 0.413. The learning quality variable has a positive but insignificant correlation with critical thinking skills with a p-value of 0.736. The learning quality variable has a positive and significant correlation to learning motivation with a p-value of 0.000.